Stone Age settlement and Holocene shore displacement in the Narva‐Luga Klint Bay area, eastern Gulf of Finland. (17th January 2013) - Rosentau, Alar; Muru, Merle; Kriiska, Aivar; Subetto, Dmitry A.; Vassiljev, Jüri; Hang, Tiit; Gerasimov, Dmitry; Nordqvist, Kerkko; Ludikova, Anna; Lõugas, Lembi; Raig, Hanna; Kihno, Kersti; et al.
<x xml:space="preserve">Abstract</x> Based on geological and archaeological proxies from NW Russia and NE Estonia and on GIS‐based modelling, shore displacement during the Stone Age in the Narva‐Luga Klint Bay area in the eastern Gulf of Finland was reconstructed. The reconstructed shore displacement curve displays three regressive phases in the Baltic Sea history, interrupted by the rapid Ancylus Lake and Litorina Sea transgressions c. 10.9–10.2 cal. ka BP and c. 8.5–7.3 cal. ka BP, respectively. During the Ancylus transgression the lake level rose 9 m at an average rate of about 13 mm per year, while during the Litorina transgression the sea level rose 8 m at an average rate of about 7 mm per year. The results show that the highest shoreline of Ancylus Lake at an altitude of 8–17 m a.s.l. was formed c. 10.2 cal. ka BP and that of the Litorina Sea at an altitude of 6–14 m a.s.l., c. 7.3 cal. ka BP. The oldest traces of human activity dated to 8.5–7.9 cal. ka BP are associated with the palaeo‐Narva River in the period of low water level in the Baltic basin at the beginning of the Litorina Sea transgression. The coastal settlement associated with the Litorina Sea lagoon, presently represented by 33 Stone Age sites, developed in the area c. 7.1 cal. ka BP and existed there for more than 2000 years. Transformation from the coastal settlement back to the river settlement indicates a change from a fishing‐and‐hunting economy to farming and animal husbandry c. 4.4 cal. ka BP, coinciding with the time of the overgrowing of the lagoon in the Narva‐Luga Klint Bay area.